THE ROLE OF THE VILLAGE IN FOREST MANAGEMENT: HUMAN RIGHTS PERSPECTIVES - Setiawan, Hary; Wisnuaji, Adam; Rif'an, Mohamad (Brawijaya Law Journal, 2016)
1945 opening noble nation Indonesia is an agreement to live together (modus vivendi) in bonding the plural nation. The Modus Vivendi, has given birth to the state's objective, which is the nation's identity and guidelines in their stride. Thus, the constitution has mandated the State to be responsible for the welfare of the people. Indonesia has the second largest tropical forest in the world with high economic value that can be managed by the state and society. This allows for the utilization of various types of plants and economic aspects of the utilization of forest products. In preparation result is a pity forests is not optimal either with intensive and with many requests deforestation or forest land conversion. Deforestation well planned and unplanned forest. On the other hand, Indonesia which acknowledges the existence of the village government and the empowerment of the rural community empowerment which is a process for making the community to improve the quality of life for the better is weak then the need for the existence of the role of government in the village of Village forest management as one of the rights of the villagers. The type of research is normative juridical. Hence this paper initiated a grand design Village forest management to complete the processing and utilization of forest products that are integrated with the role of the village government as a system intended to pengoptimalam supply chain production as one of the important indicators of development and resilience of economies in each region using variable results income forests as principal.